Characterization of Dark Septate Endophytic Fungi and Improve the Performance of Liquorice Under Organic Residue Treatment - He, Chao; Wang, Wenquan; Hou, Junling (Frontiers in Microbiology, 2019)
Dark septate endophytic (DSE) fungi is a diverse group of Ascomycetes fungi that colonize the plants roots, and may facilitate plant growth and fitness, however, their ecological roles need further clarification. This study aimed to evaluate the growth promoting effects of DSE fungi in a medicinal plant, liquorice (Glycyrrhiza uralensis), under additional organic residues. First, we isolated, identified and characterized, two DSE fungal species (Acrocalymma vagum and Paraboeremia putaminum) harboring inside the roots of liquorice growing in arid areas of China. Second, we examined the performance and rhizosphere soil parameters of liquorice plants inoculated with these fungi under additional sterilized organic residues and unsterilized organic residue (containing Trichoderma viride population) in a growth chamber. The results showed that two DSE strains could effectively colonize plant roots and formed a strain-dependent symbiosis with liquorice. DSE inoculation alone increased the plant biomass, and glycyrrhizic acid and glycyrrhizin content. It also improved the root system and N and P absorption by plants, consequently depleting these macronutrients in the soil. Residues alone increased soil organic matter, available phosphorus (P), and available nitrogen (N) content, and plant biomass, N, P, glycyrrhizic acid, and glycyrrhizin content. Mantel test and structural equation model (SEM) analysis demonstrated that DSE associated with residues significantly positively influenced soil organic matter, available P and available N, and plant biomass, glycyrrhizin, N, P, and root surface area. Variation in plant growth and glycyrrhizic acid and glycyrrhizin accumulation can be attributed to the effects of DSE inoculation. DSE associated with residues exhibited a general synergistic effect on the growth and accumulation of glycyrrhizic acid and glycyrrhizin of liquorice. We demonstrate for the first time, two DSE fungi in the liquorice roots that have potential use as promoter for the cultivation of medicinal plant.